1984
DOI: 10.1002/jbm.820180303
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in complement activation from biomaterials by removal of air nuclei from the surface roughness

Abstract: The activation of the rabbit complement system by each of three different synthetic materials is reported. Samples of each type of material were subjected to one of two different priming procedures. One priming procedure was intended to remove the air nuclei from the surface roughness of the materials; the other procedure was just the normal one. It was found that the removal of the air nuclei during priming reduced the complement activation by each of the two materials of lower surface tension, but not by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Ward et al showed that solid surface energy, regardless of the chemical composition, is of importance for the release of C5a in plasma [5]. Theyobserved, however, that the largest C5a release was detected in plasma that had been in contact with the most hydrophilic surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ward et al showed that solid surface energy, regardless of the chemical composition, is of importance for the release of C5a in plasma [5]. Theyobserved, however, that the largest C5a release was detected in plasma that had been in contact with the most hydrophilic surface.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the inert polymeric surfaces in the extracorporeal devices cause the unwanted complement activation [4]. A recent study by Ward et al showed that surface wettability may be a physical parameter of importance for complement activation [5]. Their study, using polytetrafluorethylene, silicon rubber and cellophane as substrates and measuring complement activation by C5a release in plasma, showed an increased activation with increased surface wettability.…”
mentioning
confidence: 99%
“…The modest effect which was found was attributed to the presence of a large blood-gas interface. Such an effect of air bubbles had already been documented by Ward et al (1984).…”
Section: In Vitro Evaluations Of Modified Materialsmentioning
confidence: 84%
“…Surface flaws could also contribute to complement activation by trapping air bubbles [19]. Prior studies demonstrated [20] that denucleation of silicone catheters to eliminate surface microbubbles significantly reduced the amount of C3a and C5a produced during incubation in plasma.…”
Section: Discussionmentioning
confidence: 98%